A multi-disciplinary approach to the management of intra-venous and intra- cardiac leiomymatosis: a case report - Azam Jan; Nabil Iftikhar Awan; Bakhtiar, Hira; Zahra Ahmad; Shahid Hasnain; Syed Mumtaz Anwar Shah (Journal of the Pakistan Medical Association, 2022)
Introduction: Leiomyoma is one of the most common benign smooth muscle tumor of the uterus which on rare occasions may grow into the vessels and extend up till the Inferior Vena cava or the heart and hence be referred to as Intra-Venous Leiomyomatosis and Intra-Cardiac Leiomyomatosis respectively. Case Report: We herein report a rare presentation of leiomyoma in a 46 year old female who presented with complaints of shortness of breath on exertion associated with palpitations for the past 1 year with a history of irregular menstrual bleeding. Ultrasonography of the abdomen and pelvis revealed an enlarged, distorted uterus with multiple intramural fibroids. A trans-thoracic echocardiography was then performed which showed a large right atrial mass. To investigate further, a contrast enhanced computed tomography was performed covering entire chest and upper abdomen. It showed a large lesion in right atrium of heart measuring 6x5cm.